Structural immunotherapy: Harnessing chemical design to build powerful next-generation therapeutics - Michelle H. Teplensky; Julianna N. Bourgeois; Sergej Kudruk; Sarah Hurst Petrosko; Chad A. Mirkin (Proceedings of the National Academy of Sciences, 2025)
Structural immunotherapy relies on the structural features of immunotherapeutics in addition to component identity to influence biodistribution, intra- or extracellular localization, target engagement, and processing kinetics. This strategy is poised to redefine how immunotherapeutics mobilize immunity against disease and transform our ability to harness structure–function relationships to enhance clinical outcomes.